2018
DOI: 10.26850/1678-4618eqj.v43.1.2018.p26-32
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of methylene blue using TiO2 supported in ceramic material

Abstract: The present work evaluates the use of ceramic material, produced with the aid of industrial waste through the Gel-Casting method, as a support for catalysts in the photocatalytic degradation of Methylene Blue. The analysis was carried out in a reactor containing UVC lamps through batch processing. The results show that the reaction of photocatalytic degradation of the dye presents pseudo-first order kinetics, with values of degradation between 60 and 70 %. The study evaluated the deactivation of the catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…33–39 Peters et al reported PCD of rhodamine B using TiO 2 supported in ceramic. 40 This study demonstrated that kinetic data obeyed the PFO model by fitting eqn (15) with the contact time, revealing a high correlation coefficient ( R 2 = 0.9923). Investigating PCD for ofloxacin using Mn-doped CuO photocatalyst, Liu et al showed that the PFO model exhibited good compliance with experimental results ( R 2 = 0.9813).…”
Section: The Pseudo-order Kinetic Modelmentioning
confidence: 52%
See 2 more Smart Citations
“…33–39 Peters et al reported PCD of rhodamine B using TiO 2 supported in ceramic. 40 This study demonstrated that kinetic data obeyed the PFO model by fitting eqn (15) with the contact time, revealing a high correlation coefficient ( R 2 = 0.9923). Investigating PCD for ofloxacin using Mn-doped CuO photocatalyst, Liu et al showed that the PFO model exhibited good compliance with experimental results ( R 2 = 0.9813).…”
Section: The Pseudo-order Kinetic Modelmentioning
confidence: 52%
“… 89 At low C P,0 , good fits of the PFO to experimental kinetic data presented for PCD of tetracycline ( C P,0 = 0.11 mmol L −1 ) on Fe-doping g-C 3 N 4 , 88 rhodamine B ( C P,0 = 0.01 mmol L −1 ) on TiO 2 supported porous ceramic. 40 For PCD of methylene blue on flower-like titanium nanoparticle, the compatibility between the experimental result and the PFO model was weaker with an increase in C P,0 through the reduction of R 2 value from 0.9953 down to 0.9664 corresponding to C P,0 from 0.03 up to 0.22 mmol L −1 . 90 Qu et al studied the PCD of methylene blue and congo red on photocatalytic nanoparticles derived from marine clam shells.…”
Section: Effect Of Various Factors On Photocatalytic Degradation Kine...mentioning
confidence: 91%
See 1 more Smart Citation